Federalism and Family Law in the United Arab Emirates: Untangling Conflict of Laws and Conflicts of Jurisdiction - Lena-Maria Möller (22166914) (2025)
This article investigates jurisdictional and legal conflicts within the United Arab Emirates’ (UAE) federal family law system. As a federation of seven emirates, the UAE features overlapping jurisdictions and a pluralistic legal framework in which family law is applied based on factors such as nationality, religion, and domicile. Recent legislative reforms, both federally and in the Emirate of Abu Dhabi, have added further complexity to this landscape. This article examines the substantive and jurisdictional scope of various family law codes, interpreting them through constitutional principles and relevant case law. It also highlights the recent, unexpected invocation of the doctrine of forum non conveniens, previously absent in UAE jurisprudence, in family law proceedings. Additionally, this piece addresses the challenges of managing parallel litigation across multiple legal forums. By unpacking these jurisdictional tensions, this article offers broader insights into federalism, legal pluralism, and the governance of family law in multi-jurisdictional states. Other Information Published in: Arab Law Quarterly License: https://creativecommons.org/licenses/by/4.0 See article on publisher's website: https://doi.org/10.1163/15730255-bja10196